A 2022 τ -Herculid meteor cluster from an airborne experiment: automated detection, characterization, and consequences for meteoroids - Vaubaillon, J.; Loir, C.; Ciocan, C.; Kandeepan, M.; Millet, M.; Cassagne, A.; Lacassagne, L.; Da Fonseca, P.; Zander, F.; Buttsworth, D.; Loehle, S.; Toth, J.; et al. (Astronomy and astrophysics (Berlin), 2023)
Context . The existence of meteor clusters has long since been a subject of speculation and so far only seven events have been reported, among which two involve less than five meteors, and three were seen during the Leonid storms. Aims . The 1995 outburst of Comet 73P/Schwassmann-Wachmann was predicted to result in a meteor shower in May 2022. We detected the shower, proved this to be the result of this outburst, and detected another meteor cluster during the same observation mission. Methods . The τ -Herculids meteor shower outburst on 31 May 2022 was continuously monitored for 4 h during an airborne campaign. The video data were analyzed using a recently developed computer-vision processing chain for meteor real-time detection. Results . We report and characterize the detection of a meteor cluster involving 38 fragments, detected at 06:48 UT for a total duration of 11.3 s. The derived cumulative size frequency distribution index is relatively shallow: s = 3.1. Our open-source computer-vision processing chain (named FMDT) detects 100% of the meteors that a human eye is able to detect in the video. Classical automated motion detection assuming a static camera was not suitable for the stabilized camera setup because of residual motion. Conclusions . From all reported meteor clusters, we crudely estimate their occurrence to be less than one per million observed meteors. Low heliocentric distance enhances the probability of such meteoroid self-disruption in the interplanetary space.